PENGARUH FAKTOR INTERNAL DAN EKSTERNAL TERHADAP PRESTASI BELAJAR SISWA DI SDN 29 LIMBUA KECAMATAN MINASATENE KABUPATEN PANGKEP - Muh. Yunus; Rego Devilla; Mardia . (Jurnal Ilmiah Pena: Sains dan Ilmu Pendidikan, 2019)
This study aims to: 1) Determine the influence of internal factors on student achievement of SDN 29 Limbua, Minasatene District, Pangkep Regency. 2) Determine the influence of external factors on student achievement at SDN 29 Limbua, Minasatene Subdistrict, Pangkep District. 3) Determine the influence of internal and external factors simultaneously on student achievement at SDN 29 Limbua, Minasatene District, Pangkep Regency. This study was carried out on a study population of 97 people, with a sample of 78 people. This type of research is quantitative, data collection techniques used are questionnaires and data documentation. The analysis techniques used are: 1) Descriptive statistics through percentage, inferential statistics through Multiple Linear Regression. The results showed that: Based on the Hypothesis Test Partially (Test t) With reference to the Coefficientsa table, it could be described the influence of the Internal Factor (X1), External variables (X2), on the Student Learning Achievement variable (Y), as follows: 1 ) Constant = 58,846, Positive constant value indicates positive influence of independent variables (Internal and External Factors), If the independent variable increases or influences in one unit, the dependent variable (Student Learning Achievement) will increase or be fulfilled by 58,846. 2) Internal Factor (X1) = 0,150 is the regression coefficient value of Internal Factor (X1) on student learning achievement variable (Y). This means that if the Internal Factor (X1) has a one-unit increase, then student learning achievement (Y) will experience an increase of 0,150 or 15,0%. Coefficient is positive, meaning that between Internal Factor (X1) and student learning achievement (Y) has a positive relationship, namely an increase in Internal Factors (X1) will result in an increase in student learning achievement (Y). 3) External Factors (X2) = 0.053 is a regression coefficient variable of External Factors (X2) on the variable student achievement (Y) means that if the External Factor (X2) decreases one unit, then student learning achievement (Y) will decrease by 0.053 or 05.3% coefficient is negative meaning that between External Factors (X2) and student achievement (Y) there is a negative relationship. Decreasing External Factors (X2) will result in a decrease in student learning achievement (Y). 4) Based on the hypothesis test simultaneously research (test f) is known anova table output, simultaneous testing X1, X2, towards Y, it is known that the calculated F value = 4.823> sig value 0.011, which means that H1 is accepted and H1 is rejected, which means that "All independent variables (Internal and External Factors) simultaneously have a significant effect on the dependent variable (student learning achievement)". Keywords: Internal, External Factors, Student Learning Achievement